Exploration of the form factors of turbulence kinetic energy transfer for shear exfoliation of graphene. (7th April 2021) - Liu, Kangwei; Chiang, Sum-Wai; Liang, Bin; Liang, Caiwu; Sui, Yiming; Dai, Wanyu; Wang, Min; Hu, Shengyu; Kang, Feiyu; Yang, Cheng
Abstract: Mass production of defect-free and large-lateral-size 2D materials via cost-effective methods is very important. Recently, shear exfoliation has shown great promise for large-scale production due to its simple operation, environmental-benignity and wide adaptability. However, a long-standing challenge is that with the production of more nanosheets, a ceiling yield and shattered products are encountered, which significantly limits their wider application. The method and efficiency of energy transfer in fluid is undoubtedly the key point in determining exfoliation efficiency, yet its in-depth mechanism has not yet been described. Thus, a thorough investigation of turbulence energy transfer is critically necessary. Herein, we identify two main factors that critically determine the exfoliation yield and provide a statistical analysis of the relationship between these factors and the exfoliation yield. In the initial shearing process, the coexistence of the 2D nanosheets and raw particles is the dominant factor; as time passes, the dimensional change of raw materials gradually has a greater influence on the energy transfer. These factors together lead to attenuated efficiency and a power function relationship between yield and exfoliation time. This investigation gives a statistical explanation of shear exfoliation technology for 2D material preparation and provides valuable insights for mechanical exfoliating high-quality 2D materials.